1998
DOI: 10.1002/(sici)1096-9071(199807)55:3<250::aid-jmv12>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir-resistant Varicella-Zoster virus: Phenotypic and genetic characterization

Abstract: A man with acquired immunodeficiency syndrome (AIDS) developed zoster of the right arm which was resistant clinically to acyclovir. Varicella-zoster virus (VZV) was cultured from a skin biopsy performed at the beginning of acyclovir therapy (isolate 1) and after its failure (isolate 2). The emergence of acyclovir resistance during treatment was investigated by developing a simple and rapid drug sensitivity assay based on the plaque reduction reference method. This late-antigen synthesis reduction assay involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In several studies, laboratory and clinical ACV r VZV mutants were reported (8,14,28,62). However, investigations correlating a detailed phenotype with specific mutations in the VZV TK and DNA Pol genes are lacking.…”
mentioning
confidence: 99%
“…In several studies, laboratory and clinical ACV r VZV mutants were reported (8,14,28,62). However, investigations correlating a detailed phenotype with specific mutations in the VZV TK and DNA Pol genes are lacking.…”
mentioning
confidence: 99%
“…However, this is not the case. Indeed, one can expect that most strains will be correctly identified by the colony reduction assay, for only a few strains with mutations in pol (4,14,28) have been reported, and these represent no more than 5% of all ACV r VZV strains (3,4,13,14,20,21,23,24,26,28,30,33,36,37,42,46). In addition, VZV TK mutations selected in tdk mutant bacteria can confer either deficient or altered TK phenotypes (40).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid assays for the detection of resistant VZV or HSV have been reported (1,11,13,38,41,44), and all these assays depend on cell culture methods to obtain the initial virus sample for analysis. This may be limiting and time-consuming, in particular, for VZV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sauerbrei et al, 2011 analyzed genotypically 16 VZV strains with clinical diagnosis of ACV-resistance, finding seven strains with alterations in the TK gene: three were associated to amino acid substitutions (L73I, W225R, T256M), three with stop codon generation (A163-, Q303-, N334-) and one frameshift due to a deletion of nucleotides 19-223. All of them were not previously reported, except the Q303-mutation, which has been reported in two patients with AIDS treated with ACV to control persistent zoster (Fillet et al, 1998;Saint-Léger et al, 2001). …”
Section: Vzv-resistant To Antiviral Drugsmentioning
confidence: 99%